PRODUCTION OF HALAL PRODUCTS: FARDHU KIFAYAH AMONG MUSLIM SMES, CONTRIBUTION TO MUSLIM COMMUNITIES - Siti Nor Bayaah Ahmad; Merlyn Rita Buncha; Haslinda Hasan; Irma Wani Othman; Salmah Topimin (International Journal of Accounting, Finance and Business, 2022)
The Halal industry is one of the most important national agendas in Malaysia and the government has taken many initiatives to promote the industry. This concept paper discusses the engagement of Muslim SMEs in the Halal industry as Fardhu Kifayah for the community. For this purpose, the concept of Halal, Fardhu Kifayah and SMEs is explained based on various articles and documents. The discussion in this paper concluded that religious knowledge, government support, human capital development and nurturing young Halal entrepreneurs (Halalpreneur) are among the important issues that need to be considered and supported by the respective authorities to attract Muslim SMEs for a better future of Halal industry. It is expected that the discussion in this paper will be useful to SMEs, authorities involved in Halal development and academics concerned with the concept of Halal and Fardhu Kifayah.